Development of Subsea Altimeter Sensor System (SASS) Using Portable Sonar Sensor Fish Finder Alarm for Unmanned Underwater Vehicles - Mohd Aras, Mohd Shahrieel; Mohd Nor, Arfah Syahida; Ab Rashid, Mohd Zamzuri (ACEEE, 2013)
This paper describes the development of Subsea Altimeter Sensor System (SASS) for Unmanned Underwater Vehicles (UUV) Application using portable sonar sensor fish finder alarm system. Altimeter Sensor system is used to measure the depth of water. This altimeter sensor design valid for shallow water depth ranges maximum 100 m. This SASS will be applied to Underwater Remotely Operated Vehicles (ROV) design to verify the SASS performances. Experiments conducted to measure a depth of lab test, swimming pool test and Ayer Keroh Lake test. The experiments conducted in lab pool and swimming pool to measure and estimate the error and accuracy of SASS performances because of known the depth of water. The error of Altimeter Sensor System is 10% or ± 5 cm depth and accuracy of SASS very high about 90% for the both experiments. The results on Lake of Ayer Keroh at certain point can be acceptable. The 3D design of seabed mapping is plotted using MATLAB and Excel.